“REFLEKSIV YONDASHUV”, “AXBOROT” VA “AXBOROT BILAN ISHLASH MALAKASI” TUSHUNCHALARINING ILMIY PEDAGOGIK TAHLILI - Temirov, O.M. (SCIENCE and SOCIETY, 2025)
This article analyzes the scientific and pedagogical coverage of the concepts of "reflexive approach", "information", "information skills", which form the basis of our research work, in the scientific literature. As a result of these analyses, authorial tariffs are put forward and scientifically substantiated. The article also presents some thoughts on the need for today's pedagogical education to form the skills of future teachers to work with information based on a reflexive approach.
Keywords: reflexive approach; information; information skills; information volume; information flow; analysis-synthesis; attitude; pedagogical activity; future teacher